Determinants of Financial Performance on Firm Value in Index Lq 45 Companies - Desmon Immanuel Paulus; Munasiron Miftah (Garuda Prestasi Nusantara Consulting, 2022)
This study aims to measure the effect of Liquidity (CR), Profitability (ROA) and Solvency (DER) on Firm Value (PBV) on the LQ 45 company index for the 2018 - 2020 period. The data used in this study were obtained from company annual report data that have been audited and published. In this study the population is companies listed on the Indonesia Stock Exchange (IDX). The sample is the LQ 45 company index listed on the IDX for the 2018 - 2020 observation period with a purposive sampling sampling technique so that a sample of 22 companies is obtained. This study analyzes the data using the panel data regression analysis method using the e-views version 12 software.